A new urban mobility management: car sharing and ICT - Fistola, Romano (TeMA - Journal of Land Use, Mobility and Environment, 2008)
Car sharing can today represent one valid alternative to the possession of the car for the city movement. As J. Rifkin said, we live in the “age of the use” and not of private property ownership. Unfortunately in Italy car sharing is not very spread, especially in the South of Italy. Undoubtedly, the diffusion of car sharing inside the most important Italian cities, where car mobility represents one of the main problems for urban “survival”, produces substantial advantages as regards the reduction of congestion, abatement of polluting (gas and noise) emissions, reduction of public space utilization and in general a new spur to the use of public transport. Apart from any consideration about the effects of the car sharing, it should be underlined that it represents an innovating “ethic” perspective of mobility. The diffusion of these ethic moving, in particular in Italy where the private car is traditionally still considered as “the second house” (the other good being the symbol of economic serenity), will allow to make future sceneries for mobility in the city, where environmental quality will really become an inalienable value. The article illustrates the peculiarities of car sharing; it emphasizes the undoubted advantages and tries to closely imagine a possible future of such moving way connected to the advance and the spread of the new information and communication technologies too.